Moral Disengagement and School Aggression at the Elementary SchoolLevel: The Mediating Role of Shame - Ochoa Arreola, José Alan; Tánori Quintana, Jesús; Flores Partida, Cesar Alan; Vera Noriega, José Ángel; Montoya Aguilar, José Luis (Emerging Trends in Education, 2026)
This study analyzed the relationship between moral disengagement and aggressive behaviors in elementary school students, considering the mediating role of shame and the moderating effect of sex. A cross-sectional design with a quantitative and explanatory scope was employed. The sample consisted of 562 students from fifth and sixth grade attending public schools in Sonora, Mexico (56.8% male, 43.2% female; M = 10.70 years, SD = 0.65). Validated scales measuring aggression, moral disengagement, and shame were administered. Analyses included descriptive statistics, Pearson correlations, Student’s t-tests, and a moderated mediation model using PROCESS in JASP. Results revealed positive and significant associations among moral disengagement, shame, and aggressive behaviors. Moral disengagement was directly related to aggression (β = .24), and shame partially mediated this relationship (β = .03). Significant differences by sex were observed in aggression and moral disengagement, although the interaction between moral disengagement and sex was not significant. In conclusion, moral disengagement and shame are key factors in understanding school aggression in elementary education. These findings highlight the importance of designing preventive interventions that integrate both cognitive and emotional dimensions, while also considering differences between boys and girls.